Not All Liver Abscesses Are Created Equal: The Impact of Tylosin and Antibiotic Alternatives on Bovine Liver Abscess Microbial Communities and a First Look at Bacteroidetes-Dominated Communities - Pinnell, Lee J.; Whitlow, Carla Weissend; Huebner, Katherine L.; Bryant, Tony C.; Martin, Jennifer; Belk, Keith E.; Morley, Paul S. (Frontiers in Microbiology, 2022)
Liver abscesses (LAs) are extremely prevalent in cattle, and result in significant economic losses due to liver condemnation, decreased growth and production, and lower carcass quality. LAs are commonly attributed to the transition to diets high in rapidly fermentable starch which results in rumen epithelial inflammation that allows pathogenic bacteria to gain entry to liver through transport via the hepatic portal vein. The most common intervention for LAs is the inclusion of antibiotics in feedlot diets, under the supervision of a veterinarian; this treatment is associated with reduced occurrence of LAs in this and other studies. Here, through the largest LA 16S rRNA gene sequencing study to date, we demonstrate that the inclusion of tylosin and antibiotic alternatives (the essential oil limonene, Saccharomyces cerevisiae fermentation product) had little impact on LA microbial community composition. Importantly, members of Bacteroidetes (Bacteroides spp. and Porphyromonas spp.), were identified as the dominant taxa in conjunction with low proportions of Fusobacteria in nearly a quarter (61/259) of all LA communities analyzed in this study. The relative abundances of the phyla Fusobacteria and Bacteroidetes had a strongly negative correlation, and LA microbial communities rarely contained high abundances of both of these dominant phyla. Further, based on the presence of taxa discriminant of Bacteroidetes dominated liver abscesses within over 400 bovine gut communities we provide evidence suggestive of Bacteroidetes dominated abscess communities originating in more distal portions of the bovine gut. Together, these findings suggest that some LA microbial communities may originate from portions of the gut other than the rumen, and provide indirect evidence that tylosin and other antibiotics may act indirectly on LAs by altering gut inflammation throughout the GIT to prevent bacterial translocation into the portal system.